Work ethics and its relationship with workplace ostracism and counterproductive work behaviours among nurses: a structural equation model - Nancy Sabry Elliethey; Ebtsam Aly Abou Hashish; Nariman Ahmed Mohamed Elbassal (BMC, 2024)
Abstract Background The organization's work ethics is the cornerstone to promoting positive nurses' behaviours and overcoming counterproductive ones. Purpose The current study aims to explore the relationship between work ethics (WEs) and counterproductive work behaviours (CWB) among nurses and testify to the mediating role of workplace ostracism (WO) in this relationship. Methods A descriptive correlational study was conducted in an Egyptian hospital. A convenient sample of staff nurses (N = 369) who agreed to participate in the study answered work ethics, counterproductive work behaviours, and workplace ostracism questionnaires, which were proven to be valid and reliable study measures. Descriptive and inferential statistics were applied, and relationships were presented using structural equation modelling. Ethical Considerations Ethics Committee approval, written informed consent, data privacy and confidentiality, and participants' rights to voluntary participation and withdrawal were maintained. Results The majority of nurses (78.5%) perceived a high level of work ethics while majority of nurses reporting low levels of counterproductive work behaviours and workplace ostracism (82.25%, 75.75%), respectively. In addition to the negative correlations, the findings revealed that WEs have a significant negative influence on each of CWB (β − 0.482, p < 0.005) and WO (β − 0.044, p < 0.005). The regression analysis showed that WEs can negatively predict about 15% of the variance in each of CWB and WO. On the other hand, WO has a positive effect on CWB (β 0.035, p < 0.021) and mediates the relationship between WEs and CWB. Discussion Ostracism negatively affects the attitudes of nurses, which in turn results in negative behavioural outcomes (i.e., deviant behaviour). Conclusion It is imperative for the hospital and nurse managers to establish a work environment that fosters support and cultivate work ethics and ethical work climate with the aim of managing negative work behaviours, enhancing nurses' retention and satisfaction, and eventually improving the quality of patient care.